Regional Policy and rent-seeking - Kjetil Bjorvatn; Nicola Daniele Coniglio (European Regional Science Association (ERSA), 2004)
The most important policy instrument to promote regional development in the European Union is Strucutral Funds, covering approximately a third of the EU budget. An empirical analysis demonstrates that these funds have on average been ineffective in speeding up the process of convergence with in the European Union. Only in countries with sufficiently good institutions have these funds contributed positively to regional development. Our analysis attempts to shed light on how investment subsidies may create industrialization, and more importantly, how poor quality institutions may prevent this strategy from succeeding. JEL codes: Keywords: Regional policy, rent seeking, industrialization
Keywords: 330; Regional policy; rent seeking; industrialization